THOLEIITIC AND CALC-ALKALINE MAGMATISM IN THE NORTHERN PART OF THE TIKSHOZERO GREENSTONE BELT: GEOCHEMICAL EVIDENCE OF A SUBDUCTION ENVIRONMENT - Mil'kevich R.I.; Miller Yu.V.; Glebovitskii V.A.; Bogomolov E.M.; Guseva V.F. (My University, 2003)
Supracrustal rock in the northern part of the Late Archean Tikshozero greenstone belt were determined to be of predominantly volcanic nature. The geochemistry of major, trace, and rare-earth elements and the Nd and Sr isotopic composition of these rocks suggest that they affiliate with two magmatic series, tholeiitic and calc-alkaline, and show certain features that confirm the subduction-related model for the development of the belt at 2880-2820 Ma. The tholeiitic series comprises tholeiitic basalts with layers of metamorphosed boninites and rare lenses of metamorphosed pyroxenites and peridotites, perhaps, of cumulative genesis. Judging from the high MoO, Cr, and Ni contents, the high Mg#, and REE fractionation close to the average mantle level, it is reasonable to attribute the mafic rocks to the melting products of mantle material, probably, fragments of an ophiolitic series. The rocks of the calc-alkaline series (metamorphosed dacites, andesi-dacites, and andesites) are noted for high concentrations of Al2O3, Sr, and Ba at low concentrations of Y, Yb, and Nb and Sr/Yb and Zr/Sm ratios higher than in chondrite. These rocks have positive epsilon(Nd) and low initial Sr-87/Sr-86 = 0.702. They show clearly pronounced negative anomalies at Nb and Ti but no Eu anomaly. Such geochemical characteristics are typical of island-arc tonalite-trondhjemite-dacite series (adakites), which are produced by the partial melting of basalts of the hot subducted crust at high temperatures and pressures.